Organic Field Effect Transistors II 2003
DOI: 10.1117/12.504867
|View full text |Cite
|
Sign up to set email alerts
|

Organic polymer thin film phototransistors

Abstract: We have investigated the effects of illumination, both broadband and monochromatic, on the electrical performance of organic polymer thin-film transistors (OP-TFTs). In each case, providing the illumination is sufficiently absorbed by the organic polymer, the drain current of a device biased in the OFF-state is significantly increased. We have observed increases in the OFF-state drain current as large as several orders of magnitude depending on the intensity of the incident illumination. Whereas, the drain cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Since the parameter set employed to generate the curves from is known, it can be used along with the fulfillment of f (x) (15) to verify the validity of the evolutionary procedure as a parameter extraction method in OTFTs. Experiments C and D, on the other hand, deal with the optimization and extraction of parameters of two real OTFT devices [17,73]. In Experiment C, a solution for the parameter set is also known [17], which can be compared against our results to test the effectiveness of our procedure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the parameter set employed to generate the curves from is known, it can be used along with the fulfillment of f (x) (15) to verify the validity of the evolutionary procedure as a parameter extraction method in OTFTs. Experiments C and D, on the other hand, deal with the optimization and extraction of parameters of two real OTFT devices [17,73]. In Experiment C, a solution for the parameter set is also known [17], which can be compared against our results to test the effectiveness of our procedure.…”
Section: Resultsmentioning
confidence: 99%
“…A parameter extraction procedure is now applied to current-voltage characteristics of a [poly(9,9-dioctylfluoreneco-bithiophene)] (F8T2) based OTFT designed as phototransistor [73]. The structure used by these authors corresponds to an inverted, defined-gate, gate-planarized, coplanar TFT.…”
Section: Experiments D: Parameter Extractionmentioning
confidence: 99%
“…Examining the photocurrent at the drain electrode during integration provides insights into carrier dynamics not described by steady-state phototransistor behaviour 5,48 . Figure 4a shows the integrated photogenerated charge and the EQE of the rate of integrating charge, labelled 'instantaneous EQE', during light exposure for irradiances of 40 µW cm −2 and 323 µW cm −2 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the metal oxide semiconductor field-effect transistors (MOSFETs) show outstanding characteristics in photosensitivity and responsivity [57]. Recently, we demonstrated a flexible phototransistor based on single crystalline silicon NMs.…”
Section: Silicon Nm-based Flexible Phototransistorsmentioning
confidence: 99%